Problems of Social Networking Sites in Nurturing the Aesthetic Taste of Teenagers: زهراء صبحي خزعل (Al-Academy, 2019)
With the growing number of Internet users, public and private arts activities have become increasingly popular. Adolescents have begun to establish aesthetic taste and new cultural values. This category is the most affected one by the published images and ideas especially in the social networking space and specifically the Facebook. It is the most important problem in their cultural composition. This research aims to detect the problems of social networking sites in nurturing the aesthetic taste of adolescents. The researcher used the analytical descriptive approach to obtain accurate information describing the current situation or depicting the social reality of adolescents. The research concluded that the public discourse in social media is based on a great exchange in artistic taste and its trends.